Courtship performance, not ornamentation, predicts mating success in two sister-species of wolf spider with divergent phenotypes - Hebets, Eileen A.; Oviedo-Diego, Mariela; Abdallah, Abdallah; Griger, Seth; McGinley, Rowan; Starrett, James; Bond, Jason E.; Bern, Mitch (Frontiers in Ethology, 2024)
Mate choice is posited to explain the evolution and maintenance of numerous secondary sexual traits, including ornamentation. This study explores the role of ornamentation in the mating success of two sister-species of wolf spider with divergent ornamentation. Mature male Schizocosa crassipalpata lack ornamentation while males of its closest living relative, S. bilineata, express both dark pigmentation and foreleg brushes. Following phenotypic manipulations of foreleg ornamentation -i.e. adding ornamentation in the form of dark pigment to non-ornamented males (S. crassipalpata, Aim 1) and removing ornamentation in varying degrees from highly ornamented males (S. bilineata, Aim 2 -shaving brushes; Aim 3 -shaving brushes and painting over dark pigment in vibration present/absent environments) -we found no evidence that ornamentation alone improves male mating success in either species, regardless of the vibratory signaling environment. In both S. bilineata experiments, however, higher courtship rates resulted in higher mating success, suggesting selection for courtship performance.Furthermore, females were more likely to turn, a presumed receptivity display, in response to males that courted at a higher rate. Also, similar to findings in another relative (S. stridulans), we found indications that ornamentation may function to ease a male's reliance on courtship performance -i.e., at low courtship rates, only ornamented males can secure a mating. Our phenotypic manipulations also influenced courtship behavior in S. bilineata. Shaved males began courting earlier and courted more often over a longer time than intact males, yet ultimately acquired similar matings. This increased courtship effort likely compensated for reduced ornamentation. Finally, the vibratory environment appears crucial for female-male dialogue in S. bilineata, as vibratory absent environments resulted in increased female attacks and decreased male courtship rates. Together, our data suggest that S. crassipalpata females do not possess a preference for ornamentation and that S. bilineata females do not use ornamentation alone in mating decisions. Instead, our results are consistent with a hypothesis that ornamentation in Schizocosa evolved, and is likely maintained, due to its interactions with dynamic movement displays (i.e. leg movements), which can themselves be plastically altered based on the signaler's phenotype as well as the signaling environment.